Packaging and Instagram Application Development: A Business Coaching of “Shine Icon Mora Craft” - Vitry Wijayanti; Sisdjiatmo Kusumosuwidho Widhaningrat (AIBPM Publisher, 2021)
This article describes the coaching business process carried out at an SMEs, the Shine Icon Mora Craft, to develop packaging design and Instagram account. The purpose of this research is to assist the SMEs in developing packaging designs and developing Instagram account. The research method that was used in this research is a business coaching approach. In order to get an insight into the packaging development ideas and effectiveness of the Instagram account, data obtained through surveys and in-depth. Based on the results of the research, by interviews and surveys, there are various problems faced by SMEs. But based on the limitation of the research, the research decided that the main focus is the development of packaging design and Instagram account. The packaging needed by SMEs that can protect the products inside because the nature of the products of SMEs is fragile which is the products from the SMEs is craft from polyresin, such as refrigerator magnet and statues. While for developing Instagram, account uses social media content by using visual photos to be uploaded into Instagram to attract Instagram users. The business coaching process in SMEs can be further developed to support the business optimally and give the positive impact for the SMEs.